(3eNJUQ GdadGMI GdfHWjIs - (3Ydj Hf GdMSf Hf eMeO Hf NRYd GdTQja GdMSjfjs ((3OeTb s)
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb GdSeGA aShGgf SHY SehGJ hHYO jbhd Ydi Hf GdMSjf Ef cJGH GdadGMI GdfHWjI gh CLd eG Ufa ai GdadGMGJ hbO YQHg GdaGVd CHh HcQ CMeO Hf hMTHI HCdaGX YQHjGJ hGYde Cf TLQI GdRjJhf s
(3BNQgG (B:s
(3hZjQgG ef GdOhGH GdeYjfI dfG Ydi GdadGMI hGdebhjI dfG Ydi eYGTfG hGdYUGajQ hGdcQGci hZjQgG ef CUfGa GdWGFQ aef CQGO Pdc adjCNPg ef Pdc GdcJGH s
(3HgG eWGdHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdeYGQa GdYGeIs